Decadal acidification in Atlantic and Mediterranean water masses exchanging at the Strait of Gibraltar ... : التحمض العشري في كتل المياه في المحيط الأطلسي والبحر الأبيض المتوسط التي تتبادل في مضيق جبل طارق ... - Susana Flecha; Fíz F. Pérez; Akihiko Murata; Ahmed Makaoui; I. Emma Huertas (OpenAlex, 2019)
Abstract Seawater pH is undergoing a decreasing trend due to the absorption of atmospheric CO 2 , a phenomenon known as ocean acidification (OA). Biogeochemical processes occurring naturally in the ocean also change pH and hence, for an accurate assessment of OA, the contribution of the natural component to the total pH variation must be quantified. In this work, we used 11 years (2005–2015) of biogeochemical measurements collected at the Strait of Gibraltar to estimate decadal trends of pH in two major Mediterranean water masses, the Western Mediterranean Deep Water (WMDW) and the Levantine Intermediate Water (LIW) and assess the magnitude of natural and anthropogenic components on the total pH change. The assessment was also performed in the North Atlantic Central Water (NACW) feeding the Mediterranean Sea. Our analysis revealed a significant human impact on all water masses in terms of accumulation of anthropogenic CO 2 . However, the decadal pH decline found in the WMDW and the NACW was markedly affected ... : يخضع الرقم الهيدروجيني لمياه البحر لاتجاه تنازلي بسبب امتصاص ثاني أكسيد الكربون في الغلاف الجوي، وهي ظاهرة تعرف باسم تحمض المحيطات (OA). كما أن العمليات الكيميائية الحيوية التي تحدث بشكل طبيعي في المحيط تغير أيضًا درجة الحموضة، وبالتالي، من أجل إجراء تقييم دقيق لـ OA، يجب تحديد مساهمة المكون الطبيعي في إجمالي تباين درجة الحموضة. في هذا العمل، استخدمنا 11 عامًا (2005–2015) من القياسات الجيوكيميائية الحيوية التي تم جمعها في مضيق جبل طارق لتقدير الاتجاهات العقدية لدرجة الحموضة في كتلتين مائيتين رئيسيتين في البحر الأبيض المتوسط، المياه العميقة لغرب البحر الأبيض المتوسط (WMDW) والمياه المتوسطة المشرقية (LIW) وتقييم حجم المكونات الطبيعية والبشرية على إجمالي تغير درجة الحموضة. كما تم إجراء التقييم في المياه المركزية لشمال الأطلسي (NACW) التي تغذي البحر الأبيض المتوسط. كشف تحليلنا عن تأثير بشري كبير على جميع الكتل المائية من حيث تراكم ثاني أكسيد الكربون البشري المنشأ. ومع ذلك، تأثر انخفاض درجة الحموضة العقدية الموجود في WMDW و NACW بشكل ملحوظ بالعمليات الطبيعية، والتي شكلت ما يقرب من 60 ٪ و 40 ٪ من إجمالي انخفاض ...